Spatial variability of the median age index by type for the population of the Middle Euphrates governorates for two years (1997 and 2020). (Journal of the College of Basic Education, 2024)
The age of the population is in a state of permanent change and varies from one society to another, from one region to another, and from one period of time to another, and studying it according to gender contributes to knowing these changes and drawing future plans and expectations. The governorates of the Middle Euphrates witnessed a change in the median age of the population according to gender during the years 1997 and 2020, as it was found through the application of the statistical formula for calculating the median age index that the research community is classified within the category of young societies in 1997 whose median age is (less than 20 years), It has moved to the category of mature societies in 2020, whose median age ranges between (20-29 years), with the exception of Babil Governorate, which is still among the young societies due to the high fertility of the population. The median age index also revealed a higher median age for females than it is for males during the years 1997 and 2020, and the distribution of the age index for both sexes in 1997 showed that Karbala governorate came first, then Najaf governorate followed, but the change occurred in Babel governorate, which was It occupies the third rank among males, to be the fourth among females, and Diwaniyah Governorate ranks third instead of the fourth rank among males, and this discrepancy is due to the difference in gender ratio. As for the year 2020, males were organized into three ranks, as three governorates ranked first, namely Karbala, Najaf, and Diwaniyah, with an index of median age of (20.5324) years, and Muthanna Governorate came in second place, with a very small difference in the median age index of (0, 0004) between them and the governorates of the first rank, and at the bottom of the order was the Babil governorate. As for females, Al-Diwaniyah governorate topped with an index of (21,0692) years. Followed by Muthanna Governorate with an indicator of (21,0692) years, then Karbala Governorate came in third place (21,0690) years, then Najaf Governorate (21,0689) years, and finally Babil Governorate with an indicator of median age of (19,1911) years. This change requires stakeholders and decision makers to invest this change in drawing up targeted population and development policies to achieve integration between population and development.